2015
DOI: 10.1158/1940-6207.capr-15-0025-t
|View full text |Cite
|
Sign up to set email alerts
|

Ink4a/Arf-Dependent Loss of Parietal Cells Induced by Oxidative Stress Promotes CD44-Dependent Gastric Tumorigenesis

Abstract: Loss of parietal cells initiates the development of spasmolytic polypeptide-expressing metaplasia (SPEM), a precancerous lesion in stomach. CD44 variant (CD44v) that enhances the ability to defend against reactive oxygen species (ROS) in epithelial cells is expressed de novo in SPEM of K19-Wnt1/C2mE mice, a transgenic model of gastric tumorigenesis, and is required for the efficient development of SPEM and gastric tumor in these animals. The role of ROS and its downstream signaling in CD44-dependent gastric tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In addition, CD44 appears to be involved in the pathogenesis of SPEM and to label putative gastric cancer stem cells, suggesting that it might play an important role in the process of inflammation/injury-induced carcinogenesis. 38 , 39 , 40 , 41 , 42 , 43 It also has been shown that alternative mRNA splicing produces Cd44 variant isoforms, such as Cd44v9 , which are more specifically expressed in H pylori gastritis, SPEM, and in gastric carcinomas. 40 , 41 Thus, we examined if H felis –infected Lgr5-Cre;Bmpr1a flox-flox mice show perturbations in the expression of both CD44 and of CD44v9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, CD44 appears to be involved in the pathogenesis of SPEM and to label putative gastric cancer stem cells, suggesting that it might play an important role in the process of inflammation/injury-induced carcinogenesis. 38 , 39 , 40 , 41 , 42 , 43 It also has been shown that alternative mRNA splicing produces Cd44 variant isoforms, such as Cd44v9 , which are more specifically expressed in H pylori gastritis, SPEM, and in gastric carcinomas. 40 , 41 Thus, we examined if H felis –infected Lgr5-Cre;Bmpr1a flox-flox mice show perturbations in the expression of both CD44 and of CD44v9.…”
Section: Resultsmentioning
confidence: 99%
“…Although the level of deletion of Bmpr1a in Lgr5 cells was not complete, H felis –infected Lgr5-Cre;Bmpr1a flox-flox mice showed robust phenotypic changes, suggesting that even partial inhibition of BMP signaling in Lgr5 cells can induce significant aberrations in the normal homeostatic mechanisms of the gastric mucosa. A possible explanation for this finding lies in the observation that Lgr5 cells can express growth-promoting and proinflammatory peptides, 10 , 38 , 39 , 40 , 41 , 42 , 43 factors known to play an important role in the regulation of cell proliferation and in the response of the gastric mucosa to inflammatory stimuli. It therefore is conceivable that diminished BMP signaling in Lgr5 cells could induce the expression of these molecules leading to broader and more widespread responses that might affect the biological functions not only of Lgr5 cells, but also of other adjacent cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That, together with our findings, indicates that, although gastrin is not essential for the development of SPEM, it might influence the metaplastic cascade, possibly through upregulating CLU expression in hypoacidic oxyntic glands. Upregulation of CLU could make metaplastic cells more resistant to harmful stimuli, such as oxidative stress due to chronic inflammation [ 18 ], and oxidative stress may play a central role in gastric tumorigenesis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mice given 3 consecutive daily doses of 5 mg of fully emulsified bolus doses of tamoxifen 68 had a 90% reduction in parietal cell mass in the stomach by 3 days after the first injection 26, 69. High-dose tamoxifen-treated mice also developed SPEM within 3 days of treatment with scattered proliferative SPEM cells identified.…”
Section: Murine Models Of Gastric Preneoplasiamentioning
confidence: 99%